2010
DOI: 10.1111/j.1467-9566.2009.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

The (non) use of prioritisation protocols by surgeons

Abstract: Priority setting and rationing is a dominant feature of contemporary health policy. In New Zealand, clinical priority assessment criteria (CPAC) tools have been developed to make access to elective surgery more equitable and efficient.Research was undertaken to identify how surgeons used these tools in the consultation. Forty-seven consultations with 15 different surgeons have to date been video-and audio-recorded. There were no instances where CPAC tools were explicitly used in the consultation. Drawing on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Greatbatch et al (2005) reported that British nurses operating a telephone triage service (NHS Direct) departed from protocols and tailored them to their own professional expertise. Dew et al (2010), in their study of surgeons in New Zealand, observed similar behaviours with regard to protocols designed to regulate clinical priority assessment criteria.…”
Section: Managerialism Vs Professionalismmentioning
confidence: 59%
“…Greatbatch et al (2005) reported that British nurses operating a telephone triage service (NHS Direct) departed from protocols and tailored them to their own professional expertise. Dew et al (2010), in their study of surgeons in New Zealand, observed similar behaviours with regard to protocols designed to regulate clinical priority assessment criteria.…”
Section: Managerialism Vs Professionalismmentioning
confidence: 59%
“…(2012) acknowledge, the issue of treatment fidelity presents an additional obstacle to our understanding of brief alcohol intervention effectiveness. For a variety of reasons, busy physicians dealing with alcohol in routine practice settings may deviate from guidelines and protocols of care (Moriarty et al , 2012), as happens in other areas of clinical practice (Dew et al , 2010). Thus, even when practitioners can be persuaded to engage in brief alcohol intervention, it is not possible to establish conclusively the causal chain between interventions as designed, and their subsequent outcomes (an issue that further complicates questions around which intervention components have most impact on alcohol-related outcomes (McCambridge, 2013)).…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is not unique to GPs or to AOD discussion. Non-use of guidelines and protocols is seen elsewhere in clinical practice21 and there may well be good reasons for seemingly ‘bad practice’ 34,39. Possible reasons for this should be explored to inform future strategies to enhance AOD conversations within general practice settings.…”
Section: Discussionmentioning
confidence: 99%
“…The recorded consultations used for this project are a subset of a larger dataset that was collected for two prior projects using interactional data: a study of clinical decision making in general practice and surgical consultations11 , 19 and a longitudinal study where a cohort of patients were tracked and recorded throughout an episode of care 21. In both cases, participants were informed they were being recorded for the general purpose of studying health communication.…”
Section: Introductionmentioning
confidence: 99%